Specificity of memory deficits after right or left temporal lobectomy. - Pillon B; Bazin B; Deweer B; Ehrle N; Baulac M; Dubois B; Pillon, B; Bazin, B; Deweer, B; Ehrlé, N; Baulac, M; Dubois, B (Cortex: A Journal Devoted to the Study of the Nervous System & Behavior, 1999)
An impairment of verbal memory has consistently been associated with resection of the left dominant temporal lobe, whereas non-verbal memory deficits have been less reliably observed following resection of the right temporal lobe. Such a dissociation may be due to material-specific differences of processing between verbal and non-verbal information. Alternatively, the influence of the left and right limbic structures may vary according to the stage of memory processing. The aim of the study was to test these hypotheses by comparing verbal and spatial learning in patients with left or right temporal lobe resection for intractable epilepsy, using verbal and visuospatial memory tasks with the same design: control of encoding, multiple trial learning, free and cued recall, short and long delays. The results showed: (1) a similar pattern of learning and recall in the two groups; (2) a higher performance in spatial learning for patients with left temporal lobe resection and in verbal learning for patients with right temporal lobe resection; (3) material-specific effects characterized by a higher sensitivity to cues in the verbal domain and a better retention of information during delays in the spatial domain. These results suggest parallel processing of the two temporal lobes at the various memory stages, rather than an interaction between memory stage and side of the lesion similar to that already proposed for the frontal lobes. They also confirm a double dissociation between verbal/spatial information processing and side of temporal lobe resection.